El clima organizacional en el contexto de los docentes de la Universidad Técnica de Cotopaxi. - Palma Balseca, Silvana Elizabeth (2020)
The organizational climate is a fundamental element at institutions and it is largely determined by dynamism, working place conditions, attitudes, relationships, communications and staff perceptions. The present research revealed the importance of this psychosocial element in a university institution. Its objective was to design strategies to strengthen organizational climate of teachers at Technical University of Cotopaxi. The used methodology was based on application of qualitative approach through descriptive research leading to a strategy design. As information gathering techniques, a semi-structured interview applied to Teaching Authorities and, to complement the information, a survey directed to 386 teachers from different Faculties of the University were used. The dimensions of teamwork, communication, equality, infrastructure, leadership and motivation were evaluated. It was revealed that all dimensions present an acceptable and positive perception on professors in accordance with obtained appreciations in interviews to the Authorities, who clearly specified the strengths and weaknesses of the University's work environment. It was concluded that the institution approaches the characteristics of a consultative organizational climate and participation in groups as exposed by Rensis Likert Theory. This conclusion implied to direct the proposal to strengthen both types of organizational climates present and suggest modeling and controlling management dynamism.